Aerodynamics of a Blended Wing Body Aircraft with Close-Coupled Tail: Computational Fluid Dynamics Simulations of Two Different Tail Sweep Angle Cases - Azan Haiqal Mohamed Shafari, Nur; Effendy Mohd Nasir, Rizal; Zulfazli Arief Abd Latif, Mohamad; Aiman Ahmad, M.; Wisnoe, Wirachman; Kuntjoro, Wahyu (International Journal of Engineering and Technology, 2018)
This paper presents the aerodynamic performance of Baseline V blended wing-body aircraft via Computational Fluid Dynamic (CFD) simulation. Baseline V has a set of close-coupled tail plane that can change its incidence and tilt angle for pitch and yaw control. Based on previous research, Baseline V has insufficient longitudinal stability in term of pitch moment at zero angle of attack which is negative value at zero tail incidence angles. When tail incidence is set at −10°, the moment coefficient at zero angle of attack is zero thus not sufficient for trim flight with stable pitch moment slope. This leads to the idea of sweeping the tail of the aircraft to increase moment arm. In this paper, two cases are considered which is 0° (case I) and 30° (case II) tail sweep angle in which both cases have tail incidence at −10°. NUMECA suit is used as computational tool for this simulation. The simulated environment consists of half-model Baseline V BWB in domain 20 times the length of the aircraft with body centre plane acts as a mirror. The angle of attack used for this simulation is between -10° to +17° while airspeed is fixed at 15m/s or Mach 0.05. Due to aircraft’s small mean chord and low airspeed flight, its Reynold number is low at 1.0 x 105 even at its body chord. Therefore, Laminar Navier-Stoke Equation is used for the computational simulation. Lift, drag and pitch moment coefficients with respect to angle of attack for both tail cases are computed from the simulation. The results from the CFD simulation is then compared with wind tunnel experiment results measured at AEROLAB, Universiti Teknologi Malaysia. The result shows that the trends of lift, drag and moment coefficients against angle of attack obtained from CFD simulations are similar to plots obtained from wind tunnel experiment for both tail sweep angle cases. It is found that tail sweep angle case of 30° has slightly less lift but higher drag coefficients compared with 30° tail sweep angle case while its pitch moment coefficient at zero angle of attack has now improved to allow positive trim angle of attack. However, the former has much lower maximum lift-to-drag ratio than the latter.